Biocontrol of ixodid ticks by forage legume Stylosanthes scabra (Vogel) - Khudrathulla, M D; Jagannath, M S (The Indian Journal of Animal Sciences, 2012)
The acaricidal property of Stylosanthes scabra (Vogel), a leguminous plant had been investigated. Larval and nymphal stages of commonly occurring ticks sluch as Rhipicephalus sanguineus, Boophilus microplus and Haemaphysalis intermedia were exposed to plants of various stages for different periods and their mortality was studied. Significant differences (P < 0.01) were observed in the mortality of larval and nymphal stages of ticks on plants of different ages. Highest mortality was observed on 7 month and lowest on the 10th month plants. The trapping and killing effect of S.scabra on the larvae of H. intermedia and R.sanguineus and nymphal stages of all three species of ticks was reported Â for the first time.